Fruits of victory : the Woman's Land Army of America in the Great War - Weiss, Elaine, 1952- (Potomac Books, 2008)
The women who kept the farms going while the soldiers were Over There.
Keywords: Women's Land Army of America -- History.; Women's Land Army of America; World War, 1914-1918 -- Women -- United States.; World War, 1914-1918 -- War work -- United States.; World War, 1914-1918 -- Participation, Female.; World War, 1914-1918 -- Food supply -- United States.; World War, 1914-1918 -- Economic aspects -- United States.; Women farmers -- United States -- History -- 20th century.; Guerre mondiale, 1914-1918 -- Femmes -- États-Unis.; Guerre mondiale, 1914-1918 -- Participation des civils -- États-Unis.; Guerre mondiale, 1914-1918 -- Participation des femmes.; Guerre mondiale, 1914-1918 -- Alimentation -- États-Unis.; Guerre mondiale, 1914-1918 -- Aspect économique -- États-Unis.; Agricultrices -- États-Unis -- Histoire -- 20e siècle.; HISTORY -- Military -- World War I.; Economics; Food supply; Military participation -- Female; War work; Women; Women farmers; United States; Weltkrieg -- 1914-1918; Heimatfront; Landwirtschaftlicher Betrieb; Landarbeiterin; USA; 1900-1999; History